2014
DOI: 10.1002/glia.22779
|View full text |Cite
|
Sign up to set email alerts
|

Multicolor analysis of oligodendrocyte morphology, interactions, and development with Brainbow

Abstract: Oligodendrocytes are the myelinating cells of the central nervous system. Multiple markers are available to analyze the populations of oligodendroglial cells and their precursors during development and in pathological conditions. However, the behavior of oligodendrocytes remains poorly characterized in vivo, especially at the level of individual cells. Studying this aspect has been impaired so far by the lack of suitable methods for visualizing single oligodendrocytes, their processes, and their interactions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 51 publications
6
37
3
Order By: Relevance
“…To perform our analyses, we first needed to determine the theoretical number of axons that an OL can reach, N A . Analysis of photomicrographs published by Dumas et al [7] reveals that the maximum length of the primary process of an OL in a mouse optic nerve is ~30 μm, which we take as the radius of influence of an OL. Given that axonal density in the mouse optic nerve is approximately one axon per μm 2 [11–13], we conclude that each primary process of a single OL could theoretically reach N A = 2800 axons.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To perform our analyses, we first needed to determine the theoretical number of axons that an OL can reach, N A . Analysis of photomicrographs published by Dumas et al [7] reveals that the maximum length of the primary process of an OL in a mouse optic nerve is ~30 μm, which we take as the radius of influence of an OL. Given that axonal density in the mouse optic nerve is approximately one axon per μm 2 [11–13], we conclude that each primary process of a single OL could theoretically reach N A = 2800 axons.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, Dumas and her colleagues [7] found that adjacent OLs were often observed to form juxtaposed myelin internodes on the same axon i.e. share a common set of axons (we will refer to this finding as ‘Observation B’).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The behaviors of OLs in zebrafish retinas are similar to the behaviors of OLs in the optic nerves of mice. 8,9 The lengths and number of internodes made by each OL varied greatly in different CNS regions. 38 We found that, in comparison with the spinal cord, 32,33,37 retinas tend to have longer and a greater number of internodes.…”
Section: The Behaviors Of Ols In Zebrafish Retinasmentioning
confidence: 99%
“…6,7 Oligodendrocyte precursors continue to proliferate and generate myelinating OLs into adulthood, and late-born OLs generate many more internodes, much shorter in length, than early-born OLs in mice optic nerves. 8,9 It is important to identify whether the OLs at different ages in retinas may have different behaviors regarding the number and lengths of internodes.…”
mentioning
confidence: 99%